Fotogrammetria Subacquea e Rilievo 3D di Precisione di Strutture Galleggianti o Semi-Sommerse (GEOmedia, 2014)
The article presents an innovative methodo logy for the 3D surveyingand mod eling of floating and semi-submerged objects. Photogrammetry is used for surveying both the underwater and emergedparts of the object and the two surveys are com bined together bymeans of special rigid orientation devices. As examp le, a challengingproject is repo rted, i.e. a large shipwreck (almo st 300 meters long)interested by a 52 m long leak at the waterline. The article co versthe entire workflow, starting from the preparation and data acquisitiondo wn to the realization of the digital 3D mod el by means ofdense image matching proc edures as well as deformation analysesand comp arison with the craft original plane.